Associations between primary care recorded cannabis use and mental ill health in the UK: a population-based retrospective cohort study using UK primary care data. Issue 5 (1st April 2023) - Keerthy, Deepiksana; Chandan, Joht Singh; Abramovaite, Juste; Gokhale, Krishna Margadhamane; Bandyopadhyay, Siddhartha; Day, Ed; Marwaha, Steven; Broome, Matthew R.; Nirantharakumar, Krishnarajah; Humpston, Clara
Abstract: Background: Cannabis use is a global public health issue associated with increased risks of developing mental health disorders, especially in young people. We aimed to investigate the relationships between cannabis exposure and risks of receiving mental illness diagnoses or treatment as outcomes. Methods: A population based, retrospective, open cohort study using patients recorded in 'IQVIA medical research data', a UK primary care database. Read codes were used to confirm patients with recorded exposure to cannabis use who were matched up to two unexposed patients. We examined the risk of developing three categories of mental ill health: depression, anxiety or serious mental illness (SMI). Results: At study entry, the exposed cohort had an increased likelihood of having experienced mental ill health [odds ratio (OR) 4.13; 95% confidence interval (CI) 3.99–4.27] and mental ill health-related prescription (OR 2.95; 95% CI 2.86–3.05) compared to the unexposed group. During the study period we found that exposure to cannabis was associated with an increased risk of developing any mental disorder [adjusted hazard ratio (aHR) 2.73; 95% CI 2.59–2.88], also noted when examining by subtype of disorder: anxiety (aHR 2.46; 95% CI 2.29–2.64), depression (aHR 2.34; 95% CI 2.20–2.49) and SMI (aHR 6.41; 95% CI 5.42–7.57). These results remained robust in sensitivity analyses. Conclusion: These findings point to the potential need for a public health approach to the management of people misusing cannabis. However, there is a gross under-recording of cannabis use in GP records, as seen by the prevalence of recorded cannabis exposure substantially lower than self-reported survey records.